Tgx-12ctgx+1=0 cosx ≠ 0; sinx ≠ 0
<span>tg</span>²<span>x + tgx - 12 = 0
(tgx + 4)(tgx - 3) = 0
1) tgx = -4
x</span>₁<span> = arctg (-4) + </span>πn = -arctg 4 + πn; n∈Z
2) tgx = 3
x₂ = arctg 3 + πk; k∈Z
Вот, буду благодарна если поблагодарите за ответ!
Y=x^4-8x^2-9. [-1,1],
y1=4x³-16x
<span>4x³-16x=0
</span>4x(x²-4)=0
x=0 x=-2 x=2
x=-1 y=1-8-9=-16 <span>наименьшее
</span>x=0 y=-9 <span>наибольшее
</span>y=x^4-8x^2-9.[3,5];
x=3 y=81-72-9=0 наименьшее
x=5 y=625-200-9=416
y=<span>x^3/3-5x^2/2+6x+10 [0,1]
</span>y1=x²-5x+6
x<span>²-5x+6=0
</span>x=2 x=3
x=0 y=10 наименьшее
x=1 y=18 5/6 наибольшее
y=x^3/3-5x^2/2+6x+10[0;2,5]
x=0 y=10
<span>x=2 y=34 2/3
</span><span>x=2.5 y=84 3/8</span>
Х/300=50-20
х/300=30
х=30×300
х=9000